Strengthening of deep RC coupling beams with FRP composites: A numerical study. (May 2023) - Heydari, Pooria; Mostofinejad, Davood; Mostafaei, Hasan; Ahmadi, Hajar
Abstract: Currently, most buildings have earthquake-resistant systems such as coupled shear walls and couple beams, designed based on previous code specifications. Also, due to specifications of new codes, diagonal reinforcement details in coupled beams are introduced, which due to the high reinforcement congestion, creates problems in fabrication and pouring. The main goal of this paper is to numerically study retrofitting with polymer composites reinforced with carbon fiber with external bonding for reinforced concrete coupling beams. The previous studies are divided into three categories. The first part concerns using externally bonded composite FRPs and the effect of fiber arrangement and thickness on the coupled beam behavior. The maximum displacement ductility in shear reinforcement patterns belonged to I and 2I patterns, which had the maximum ductility coefficients of 7.04 and 8.87. By comparing 7 CFRP reinforcement patterns, results showed that due to the mixed failure mode (flexural-shear) of the coupling beam, the U-X reinforcement pattern increased the load-bearing capacity by 18% compared with the base sample. By using suitable anchorage and preventing premature debonding, this method could be introduced as an effective method for improving the coupling beam's behavior. In the second category, reinforcement with composite FRPs was compared with diagonal reinforcement and strengthening by installing steel plates and the accompanying behavior diagrams were given. Compared with other reinforcement methods in terms of load-bearing capacity and ductility, the specimen reinforced with CFRP and steel plates had a 49% and 70.4% increased load-bearing capacity of the control specimen. Among the studied specimens, the best performance belonged to the specimen with diagonal reinforcements, which had an increased load-bearing capacity and ductility of 124% and 4.2% compared with the base specimen. Finally, the third part is about the effective parameters of the coupling beam such as span length to height ratio and longitudinal reinforcement value regarding coupling beam behavior.